KAJIAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN TANAMAN GARUT (Maranta arundinacea L.) - Pius K Boli Udak; Dewi Ratna Nurhayati; SaifuI Bahri (Innofarm:Jurnal Inovasi Pertanian, 2021)
The research on "A Study of Manure Dosage on the Growth of Garut (Maranta Arudinacea L)" was carried out from April 25, 2021 to July 19, 2021 at the Jaya Wijaya Research Center, Faculty of Agriculture, Slamet Riyadi University, Surakarta, which is located in Kadipiro Village, Banjarsari District, Kota Surakarta, Central Java 57136 with an altitude of ± 105 mdpl.. This study aims to examine the appropriate dose of manure on the growth of arrowroot plants. This study used a completely randomized design (CRD), with a single factor, namely the dose and type of organic fertilizer. The treatments in this study were chicken manure 160 grams/plant (A1), chicken manure 320 grams/plant (A2), chicken manure 480 grams/plant (A3), Chicken manure 640 grams/plant (A4), Goat manure 0 grams/plant (K0), Goat manure 240 grams/plant (K1), Goat manure 480 grams/plant (K2), Goat manure 720 grams/ plants (K3) and goat manure 960 grams/plant (K4). Each treatment was repeated 3 times, so there were 30 polybags. Data were analyzed using Analysis of Variety, followed by Honest Significant Difference Test at 5% level. The results showed that the treatment of manure had a very significant effect on plant growth. Treatment (A2) gave the highest yield at plant height of 87.50 cm and number of leaves of 27.25 strands. Treatment (A4) gave the highest yield of 5.25 units of tiller and 664.50 gram of wet stover weight. Treatment (A1) gave the highest yield on the dry weight of the stove, which was 113.75 grams. The greenness of the treatment leaves (A1), (A2), (A3), (A4), (K1), (K2), (K3) and (K4) resulted in the same average value of 5.